Political Parties in Kosovo, Organizational Structure and Their Internal Democracy - Zejnullahi, Veton (European Journal of Multidisciplinary Studies, 2016)
The collapse of communism in the former Eastern bloc , which was followed by the establishment of democracies popular and holding free elections to the parliaments of the countries concerned had its impact in Kosovo , which although occupied accepted among first democracy in the former Yugoslavia , which was followed by the creation of political parties at that time. The role of political parties in the years of occupation there was a genuine character of party activity as a result of the occupation, because the main word on Kosovo was Serbian government, installed after violent suppression of Kosovo’s autonomy in 1989. Political parties in general It served as a national movement, some of which joined the Kosovo Albanians by articulating their demands for freedom and independence. This included organizing parties in Kosovo and the Albanian parties in other areas in the former Yugoslavia was organized by the Coordination Council of Albanian Parties. End of the war in 1999 brought a completely new situation, changing political scene with the formation of more political parties, as well as providing more opportunities for a better organization of the political scene. Some of the political parties no longer exist, while others have a very small number of members. The formation of new parties expected profiling of political scene, however, serves only their declarative they are right or left, in most cases a proper profiling has not happened yet. Political parties in Kosovo even after so many years of activity apparently still in the phase of consolidation but also in search of their identity.